2021
DOI: 10.1186/s12915-021-01102-4
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution structure of the amino acid transporter AdiC reveals insights into the role of water molecules and networks in oligomerization and substrate binding

Abstract: Background The L-arginine/agmatine transporter AdiC is part of the arginine-dependent extreme acid resistance system of the bacterium Escherichia coli and its pathogenic varieties such as strain E. coli O157:H7. At the present time, there is a lack of knowledge concerning the role of water molecules and networks for the structure and function of AdiC, and solute transporters in general. Results The structure of the L-arginine/agmatine transporter A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…Fig. 6 illustrates four superimposed partial structures of AdiC and related transporters (Shaffer et al, 2009, Gao et al, 2010, Errasti-Murugarren et al, 2019, Ilgu et al, 2021), in which the orientation of helix 6 or its counterpart shown in Fig. 6A,B is represented by a vector that is color-coded for a specific structural state (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fig. 6 illustrates four superimposed partial structures of AdiC and related transporters (Shaffer et al, 2009, Gao et al, 2010, Errasti-Murugarren et al, 2019, Ilgu et al, 2021), in which the orientation of helix 6 or its counterpart shown in Fig. 6A,B is represented by a vector that is color-coded for a specific structural state (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To examine conformational changes of AdiC, we chose to monitor helix 6a in one of its subunits (Fig. 1D,E) (Gao et al, 2009, Fang et al, 2009, Gao et al, 2010, Kowalczyk et al, 2011, Ilgu et al, 2016, Ilgu et al, 2021). This helix adopts differing spatial orientations among different known structural states in AdiC (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A shows a set of intensity traces recorded at a rate of 10 ms per frame from a bifunctional rhodamine attached to helix-6A of AdiC, which was inserted into nanodiscs, attached to a coverslip, and exposed to 50 μM of the ligand Agm 2+ . Judging from crystal structures, helix-6A adopts different orientations in different states (Gao et al, 2009, Fang et al, 2009, Gao et al, 2010, Kowalczyk et al, 2011, Ilgu et al, 2016, Ilgu et al, 2021). Unless specified otherwise, all references to AdiC, a structural dimer, are in the context of an independent functional subunit; Agm 2+ or Arg + are referred to as substrate and ligand in the context of their transport and binding, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…1B), under which is an illustrative color-coded state profile. The conformational states are shown in the form of electron density maps (PDB: 7O82, 3L1L, 3GIA, 6F2G) (Shaffer et al, 2009, Gao et al, 2010, Errasti-Murugarren et al, 2019, Ilgu et al, 2021), colored for states as for the state profile trace. Two segments of video frames from the movie are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%